2014
DOI: 10.2147/jpr.s69011
|View full text |Cite
|
Sign up to set email alerts
|

Use of the painDETECT tool in rheumatoid arthritis suggests neuropathic and sensitization components in pain reporting

Abstract: Rheumatoid arthritis (RA) is an inflammatory autoimmune condition typified by systemic inflammation targeted toward synovial joints. Inhibition of proinflammatory networks by disease-modifying antirheumatic drugs, eg, methotrexate and biologic therapies, including tumor necrosis factor-α inhibitors, often leads to suppression of disease activity observed at the clinical level. However, despite the era of widespread use of disease-modifying treatments, there remain significant groups of patients who continue to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 28 publications
2
30
0
2
Order By: Relevance
“…The 17 % proportion of RA patients with likely NP found in this study was very similar to the 19 % prevalence reported by Meirinhos et al [ 21 ]. Conversely, Ahmed et al [ 20 ] reported that 28 % of RA patients had possible NP symptoms and 5 % were likely to be experiencing NP symptoms according to the painDETECT. The relatively high proportion of patients (36 %) with NP in the study by Perrot et al [ 22 ] may have resulted from their use of the DN4 questionnaire, which tends to have a high sensitivity but low specificity in identifying NP [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 17 % proportion of RA patients with likely NP found in this study was very similar to the 19 % prevalence reported by Meirinhos et al [ 21 ]. Conversely, Ahmed et al [ 20 ] reported that 28 % of RA patients had possible NP symptoms and 5 % were likely to be experiencing NP symptoms according to the painDETECT. The relatively high proportion of patients (36 %) with NP in the study by Perrot et al [ 22 ] may have resulted from their use of the DN4 questionnaire, which tends to have a high sensitivity but low specificity in identifying NP [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have specifically examined the prevalence of NP features in RA. Only three studies in (subsamples of) RA patients estimated the prevalence of NP using screening tools such as the painDETECT [ 20 22 ]. However, prevalence rates of likely NP varied widely between 5 % and 36 %.…”
Section: Introductionmentioning
confidence: 99%
“…These patients also had higher disease activity scores independently from inflammatory origins but related to the non-nociceptive pain [30]. On the other hand, higher levels of pain were reported to be unrelated to disease activity as assessed by Disease Activity Score 28 [31]. …”
Section: Discussionmentioning
confidence: 99%
“… 46 Research of neuropathic pain features in other chronic pain and rheumatic conditions has expanded the applicability of PDQ. 23 24 53 54 The PDQ consists of nine items of which seven are somatosensory descriptor items, and two items relate to the spatial (radiating) and temporal pain characteristics. For screening purposes, PDQ cut-off scores ≤12 (a neuropathic component is unlikely) and ≥19 (a neuropathic component is likely) have been found to be appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…These are also common pain qualities in patients with fibromyalgia 23 and frequently reported by rheumatic patients. 24–26 In some individuals, CS seems to develop into a state of chronic widespread pain (CWP) fully uncoupled from inflammatory activity. The mechanisms behind CWP is sparsely elucidated but may involve maladaptive neuroplasticity and cortical reorganisation of the somatosensory and motor systems, 26 27 aberrant peripheral inputs to central nervous system, 28 modulation of glia cell function, 29 and disruption of descending inhibitory and facilitating control.…”
Section: Introductionmentioning
confidence: 99%